2020
DOI: 10.1038/s41436-019-0688-6
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Outcomes Data Collection Instrument is a Useful Patient-Reported Outcome Measure for Physical Function in Children with Osteogenesis Imperfecta

Abstract: Purpose: Patient-reported outcome measures (PROMs) are increasingly recognized as valuable endpoints in clinical trials. Pediatric Outcomes Data Collection Instrument (PODCI) is a PROM utilized in children with musculoskeletal disorders. We evaluated the validity and reliability of PODCI in children with osteogenesis imperfecta (OI). Methods: Physical functioning and psychological well-being were assessed using PODCI in a large cohort of children enrolled in a multicenter study conducted by the Brittle Bone Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…20 Therefore, to understand the utility of SF-12v2 in OI, we utilized data from a large cohort of adults Our group has previously validated a generic PROM, the PODCI, for use in children with OI. 14 Similar to our findings on the PODCI, this study revealed that PCS scores were representative of the known clinical severity of OI, with the mean score in OI type III (severe) being the lowest (worst) and mean scores in OI type I (mild) being the highest.…”
Section: Clinical Trial Readinesssupporting
confidence: 88%
See 2 more Smart Citations
“…20 Therefore, to understand the utility of SF-12v2 in OI, we utilized data from a large cohort of adults Our group has previously validated a generic PROM, the PODCI, for use in children with OI. 14 Similar to our findings on the PODCI, this study revealed that PCS scores were representative of the known clinical severity of OI, with the mean score in OI type III (severe) being the lowest (worst) and mean scores in OI type I (mild) being the highest.…”
Section: Clinical Trial Readinesssupporting
confidence: 88%
“…[9][10][11][12][13] To address the paucity of validated PROMs for rare skeletal disorders, our group recently investigated the utility of the pediatric outcomes data collection instrument (PODCI), a generic functional status PROM used in children with musculoskeletal disorders, in children with OI. [14][15][16] Using data from a large, multicenter, observational, natural history study of OI conducted by the National Institutes of Health (NIH) Rare Disease Clinical Research Network's (RDCRN) Brittle Bone Disorders Consortium (BBDC), we analyzed PODCI responses from 418 children with OI. We showed that this generic PROM was a useful measure of physical function in children with OI and that the physical function scores correlated with corresponding scales of an observer-rated outcome measure, the Brief Assessment of Motor Function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, updated research demonstrated that the pediatric outcomes data collection instrument could be a reliable measure of physical functioning in children with OI (34). It offers valuable information about patient-reported systemic health status.…”
Section: Discussionmentioning
confidence: 99%
“…Publicly funded gene screening is offered to New Zealand breast cancer patients by Genetic Health Service New Zealand (GHSNZ) if they fulfil testing criteria provided by eviQ Cancer Genetics (Breast and Ovarian Referral Guidelines— https://www.eviq.org.au/ ). Based on these guidelines, individuals may meet criteria based on their tumour pathology (negative status for oestrogen receptor, progesterone receptor and ERBB2/HER2 expression), or where a BRCA1 and BRCA2 pathogenic variant probability of 10% or more is calculated using a validated pathogenic variant prediction tool, such as the BOADICEA assessment programme [ 10 ]. Currently, approximately 9% of eligible New Zealand patients who have undergone genetic screening were found to carry a clinically actionable genetic variant in BRCA1 or BRCA2 .…”
Section: Introductionmentioning
confidence: 99%